Menopausal hormone therapy in questions and answers – a manual for physicians of various specialties - Paszkowski, Tomasz; Bińkowska, Małgorzata; Dębski, Romuald; Krzyczkowska-Sendrakowska, Magdalena; Skrzypulec-Plinta, Violetta; Zgliczyński, Wojciech (Menopause Review/Przegląd Menopauzalny, 2019)
This manual has been prepared by the Expert Team of the Polish Menopause and Andropause Society for physicians representing various medical specialties who see patients with menopausal symptoms in their daily practice. In order to make the manual as practical as possible, the current state of knowledge on menopausal hormone therapy (MHT) is presented in the form of questions and answers. They address issues which are essential for initiating and managing MHT based on the most up-to-date treatment algorithms and, at the same time, in line with the old maxim “primum non nocere”.